Message from Orginizing Committee - Bambang Pontjo Priosoeryanto (Hemera Zoa, 2018)
Dear Colleagues,     It gives us immense pleasure to inform you that Indonesian Veterinary Medical Association (IVMA) is organizing the 20th Federation of Asian Veterinary Associations Congress (FAVA Congress) & the 18th Indonesian Veterinary Medical Association Congress (IVMA Congress) an International Congress, Seminar and Workshop. The event will be held in the Nusa Dua, Bali, the very famous paradise island and international tourist destination from October 30th to November 3rd, 2018.     The current congress will be enriched and compose of several satellite meeting of international and national veterinary organizations such as The 40th FAVA Council Meeting, 15th IVMA International Veterinary Scientific Conference and Animal Health Expo, The 2nd JSPS Core-to-Core Program Tripartite Meeting, The 1st FAVA-AVA Joint Meeting, ASEAN Veterinary Statutory Body Network (AVSBN) Meeting, Meeting of IVMA's Organizations of Veterinary Specialty and Scientific Interest Groups, Indonesian Animal Hospital Association (ARSHI) Meeting and the 16th PIDHI Meeting. It is expected to be a big event in veterinary field in 2018 with expected more than 1,000 participants coming around the country as well as foreign participants from Asian countries and other continents.     In this opportunity, a very basic Veterinary Role as an important profession was chosen as the theme of the present event “To Serve Mankind through Animal Kingdom”. The Organizing Committee cordially invites all the Veterinarian, Veterinary and Biomedical Scientists, Animal Husbandry practitioners, Human Medical, Academicians, Scholars and other related professions in Asia and other continents to take part in this event.     The Congress and Scientific seminar will focus on the improvement of the role of veterinary professions in Asian countries as well as recent developments, trends and technologies available for disease prevention, diagnosis, treatments as well as productivity and quality of animals and animal products. The main objective of this event is to bridging government-academicians–business sector and public participation to achieve the goal for better serve and better quality of life. Thank you.Sincerely, Bambang Pontjo Priosoeryanto, Chairman of the Organizing Committee